ANALYSIS OF SAFETY OF NEOADJUVANT CHEMORADIOTHERAPY IN PATIENTS WITH LOCALLY ADVANCED GASTRIC CANCER (RESULTS OF A MULTICENTER RANDOMIZED TRIAL) - V. Yu. Skoropad; S. G. Afanasyev; S. V. Gamayunov; P. V. Sokolov; V. A. Karov; L. N. Titova; N. K. Silanteva; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2020)
The purpose of the study was to immediate results of neoadjuvant chemoradiotherapy in patients with locally advanced gastric cancer were analyzed in a multicenter randomized trial. Material and Methods. The comparative analysis of neoadjuvant chemotherapy regimens, toxicity and postoperative complications was carried out. Patients of the study group received conformal radiation therapy (46 Gy in 2 Gy daily fractions) concurrently with chemotherapy with Capecitabine at a dose of 1850 mg/m2 divided in two equal doses during the course of radiation therapy, and Oxaliplatin at a dose of 85 mg/m2 on days 1 and 21. After an interval of 4–6 weeks and a control examination, in the absence of evident disease progression, patients were scheduled for surgery (gastrectomy or subtotal gastrectomy with D2 lymph node dissection) and 4 cycles of adjuvant chemotherapy according to the FOLFOX4 or CAPOX regimen. The treatment program for patients in the control group included surgery (gastrectomy or subtotal gastrectomy with D2 lymph node dissection) after randomization, and 6 cycles of adjuvant chemotherapy using the same regimens. The study included 70 patients with an equal distribution between groups. Results. Among the patients of the study group, grade 1 and 2 toxicity was the most common; grade 3 toxicity occurred in 9 cases; grade 4 and 5 toxicity was not observed. Among the manifestations of hematological toxicity, thrombocytopenia and leukopenia were the most common (57–60 % of patients), and grade 3 hematological toxicity was observed in 6 (17.1 %) cases. Among the manifestations of gastrointestinal toxicity, nausea, vomiting and decreased appetite prevailed; grade 3 toxicity was observed only in 3 (8.6 %) cases. The radiation component of neoadjuvant therapy was completed in 32 (91 %) patients. Both protocol-prescribed oxaliplatin infusions were performed in 34 (97 %) patients. Changes in capecitabine administration were required in 8 patients. Immediately before surgery, some patients had grade 1–2 toxicity, which did not prevent performing surgery. There were no statistically significant differences in the frequency and severity of complications in the early postoperative period between the comparison groups. Grade 1–2 postoperative complications were the most common.